2015
DOI: 10.1159/000435907
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Modifies the Effect of Fitness on Heart Rate Indices during Exercise Stress Testing in Asymptomatic Individuals

Abstract: Objective: To assess the impact of aerobic fitness on exercise heart rate (HR) indices in an asymptomatic cohort across different body mass index (BMI) categories. Methods: We performed a cross-sectional analysis of 506 working-class Brazilian subjects, free of known clinical cardiovascular disease (e.g. ischemic heart disease and stroke) who underwent an exercise stress test. Results: There was a significant trend towards decreased HR at peak exercise, HR recovery and chronotropic index (CI) measures as BMI i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…In this study, after adjusting for covariates using hierarchical multiple regression percentage body fat, MET, and age were negative determinants of 1-minute HRR. The results are in line with three previous studies 10,13 , that a higher percentage body fat and age were associated with an impaired HRR. Moreover, a higher maximal MET level was associated with a better HRR following 1-minute post treadmill exercise testing.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, after adjusting for covariates using hierarchical multiple regression percentage body fat, MET, and age were negative determinants of 1-minute HRR. The results are in line with three previous studies 10,13 , that a higher percentage body fat and age were associated with an impaired HRR. Moreover, a higher maximal MET level was associated with a better HRR following 1-minute post treadmill exercise testing.…”
Section: Discussionsupporting
confidence: 93%
“…In obese subjects, this impairment is reflected by reduced parasympathetic nervous system function and/or sympathetic nervous system overactivity 9 . Furthermore, a study in obese subjects with low levels of physical fitness revealed an impaired chronotropic index and HRR during and after exercise stress testing 10 . Several studies have shown that parameters of obesity negatively affect HRR following exercise [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the obese subjects had a 20% higher HR than the other two BMI groups. Previous studies reported that obese people have an elevated resting HR [43][44][45][46], which puts them at increased risk for cardiometabolic problems [47][48][49]. Cardiorespiratory fitness, which is more common among people of lower BMI, has been associated with a decrease in resting heart rate [50,51].…”
Section: Plos Onementioning
confidence: 99%